Transcriptome and metabolome analysis of flavonol synthesis in apricot fruits - Han, Xueping; Wang, Jinzheng; Wang, Guiping; Dong, Fang; Nie, Peixian; Xue, Xiaomin (Frontiers in Plant Science, 2023)
Apricot fruits are edible and serve as a source of medicinal compounds. Flavonols are important plant secondary metabolites that have antioxidant and antitumor effects and may promote cardiovascular health. To decipher the regulation of flavonol synthesis in apricot (Prunus armeniaca L.), we comprehensively analyzed the ‘Katy’ and ‘Kuijin’ fruit pulp metabolomes and transcriptomes at three developmental stages. The differences in the metabolite contents between stages (of the same cultivar) and between cultivars (at the same stage) revealed decreases in the flavonoid content as fruits developed (i.e., from 0.28 mg/g to 0.12 mg/g in ‘Kuijin’ and from 0.23 mg/g to 0.05 mg/g in ‘Katy’). Ten flavonols were more abundant in KuijinA than in the other samples. The weighted gene co-expression network analysis showed that the ‘turquoise’ module genes were highly correlated with flavonol contents (P < 0.001). Analyses of the correlations between gene expression levels and the contents of individual flavonols suggested that three key structural genes and 9 genes encoding transcription factors (3 MYBs, 1 bHLHs, 2ERFs, 2NAC and 1WRKY) were closely associated with the synthesis of 10 flavonols. This study identified the main factors responsible for the increased production of flavonols in young apricot fruits.